Produção, consumo e circulação de alimentos durante a seca: um estudo sobre famílias lavradoras em Medina, Vale do Jequitinhonha. - Lucas Fernandes Barbosa (2020)
This dissertation aimed to investigate the repercussion of water scarcity on the production, consumption and circulation of food by the rural population of the municipality of Medina, Jequitinhonha valley, northeast Minas Gerais. The work is organized in two major parts: the first deals with social theories and theoretical elements related to the population and region researched; the second part concerns the collection and analysis of empirical results. The research was based on the articulation of secondary data sources, the application of semi- oriented questionnaires and interviews with specialist farmers living in six rural communities. The results indicated the daily presence of shortages in food production, motivated by factors such as: irregular rainfall; absence or low participation of the researched population in programs for living with the semi-arid; disappearance of natural sources for water supply; and the regular presence of tank truck supply in the researched communities. The lack of water had an explicit impact on the reduction of productive practices for self-consumption and alternativity of family production, reflecting the condition of food sovereignty of the families, aggravated by the reduction of social public policies; fluctuation of food prices for purchase; and climate change. The results indicated that short circuits are essential for the circulation of food produced by family agriculture in Medina, especially the street fair, guaranteeing a regionalized diet and the supply of one third of the municipality's urban population, and income for rural families to access goods and services.